The Implementation Of Inquiry-Based Learning For The Teaching English At SMP Muhammadiyah 6 Surakarta In 2015/2016 Academic Year - Ariani, Jessy Setya; , Prof. Dr. Endang Fauziati, M.Hum; , Aryati Prasetyarini, S.Pd, M.Pd (2016)
This study aims to describe the implementation of Inquiry-based Learning for teaching English at SMP Muhammadiyah 6 Surakarta in 2015/2016 academic year which is divided into components of teaching namely learning objectives, classroom procedures, classroom techniques, the roles of instructional materials, teacher's roles, student's roles, media, and types of assessment. The type of this research is naturalistic qualitative research. The methods of collecting data are observation, interview, documentation, and recording. The researcher uses reduction of data, display of data, and conclusion/verification for technique of analyzing data. The result of this study shows that; (1) There are two types of learning objectives in teaching English that are general and specific learning objectives, (2) The classroom procedures applied are exploration, elaboration, and confirmation, (3) The classroom techniques used are oral repetition, skimming and scanning, questioning, giving assignment, and individual assignment, (4) The roles of instructional material are: the materials facilitate the communicative abilities of interpretation, expression, and negotiation; materials focus on understandable and relevant communication rather than on grammatical form; and materials command the learners' interests and involve their intelligence and creativity, (5) Teacher's roles are as a materials developer, provider of accurate language models, motivator, evaluator, counselor and friend, (6) Student's roles are as planner of his or her own learning program and thus ultimately assumes responsibility for what he or she does in classroom, monitor and evaluator of his or her own progress, and tutor of other learners, (7) The media used is picture when teaching learning process, (8) Types of assessment are written and oral. Key words: Inquiry-based Learning, teaching English